Prevention of child mental health problems in Southeastern Europe: a multicentre sequential study to adapt, optimise and test the parenting programme 'Parenting for Lifelong Health for Young Children', protocol for stage 1, the feasibility study. Issue 1 (25th January 2019) - Frantz, Inga; Foran, Heather M; Lachman, Jamie M; Jansen, Elena; Hutchings, Judy; Băban, Adriana; Fang, Xiangming; Gardner, Frances; Lesco, Galina; Raleva, Marija; Ward, Catherine L; Williams, Margiad Elen; et al.
Abstract : Introduction: Families in low-income and middle-income countries (LMICs) face multiple challenges (eg, poverty and adverse childhood experiences) that increase the risk for child mental health problems, while the context may provide them with few resources. Existing prevention-oriented parenting programmes have been shown to be effective in reducing child behaviour problems and associated risk factors. This project has the overall goal of adapting, implementing and testing a parenting intervention in three Southeastern European LMIC and uses the Multiphase Optimisation Strategy and dimensions of the Reach, Effectiveness, Adoption, Implementation and Maintenance framework. It is implemented over three phases: (1) preparation, (2) optimisation and (3) evaluation. The preparation phase, the subject of this paper, involves the adaptation and feasibility piloting of the parenting programme. Methods and analysis: This protocol describes the assessment of an evidence-informed indicated prevention programme for families with children aged 2–9 years (Parenting for Lifelong Health for Young Children) for implementation in FYR of Macedonia, Republic of Moldova and Romania. In this phase, officials, experts, parents and practitioners are interviewed to explore their views of suitability and needs for further adaptation. In addition, a small pre–post pilot study will test the feasibility of the programme and its implementation as well as the evaluation measures in the three countries with 40 families per country site (n=120). Quantitative data analysis will comprise a psychometric analysis of measures, testing pre–post differences using ANCOVA, χ 2 tests and regression analysis. For qualitative data analysis, a thematic approach within an experiential framework will be applied. Ethics and dissemination: The ethics review board of the Alpen-Adria University Klagenfurt and ethical review boards in the three LMIC sites have approved the study. Trial registration number: NCT03552250 .